Complementary Therapies for the Body, Mind and Soul - Saad, Marcelo (IntechOpen, 2015)
Complementary Therapies (CT) refers to the practices, products, or health systems that are outside the realm of conventional medicine, used to treat disease or to promote health and well-being. Defining CT is difficult, because the field is very broad and constantly changing. The title of this book includes the words body, mind, and soul. The body and the mind (and their reciprocal relations) have been extensively studied scientifically. What about the soul? The book brings some points about this new ground in CT. We hope you find in the present work the sincere desire to collaborate with the dissemination of knowledge. May this book be useful and pleasant to you.